Cyclophilin B control of lysine post-translational modifications of skin type I collagen. - Masahiko Terajima; Yuki Taga; Wayne A Cabral; Ying Liu; Masako Nagasawa; Noriko Sumida; Yukako Kayashima; Prashant Chandrasekaran; Lin Han; Nobuyo Maeda; Irina Perdivara; Shunji Hattori; et al. (PLoS Genetics, 2019)
Covalent intermolecular cross-linking of collagen is essential for tissue stability. Recent studies have demonstrated that cyclophilin B (CypB), an endoplasmic reticulum (ER)-resident peptidyl-prolyl cis-trans isomerase, modulates lysine (Lys) hydroxylation of type I collagen impacting cross-linking chemistry. However, the extent of modulation, the molecular mechanism and the functional outcome in tissues are not well understood. Here, we report that, in CypB null (KO) mouse skin, two unusual collagen cross-links lacking Lys hydroxylation are formed while neither was detected in wild type (WT) or heterozygous (Het) mice. Mass spectrometric analysis of type I collagen showed that none of the telopeptidyl Lys was hydroxylated in KO or WT/Het mice. Hydroxylation of the helical cross-linking Lys residues was almost complete in WT/Het but was markedly diminished in KO. Lys hydroxylation at other sites was also lower in KO but to a lesser extent. A key glycosylation site, α1(I) Lys-87, was underglycosylated while other sites were mostly overglycosylated in KO. Despite these findings, lysyl hydroxylases and glycosyltransferase 25 domain 1 levels were significantly higher in KO than WT/Het. However, the components of ER chaperone complex that positively or negatively regulates lysyl hydroxylase activities were severely reduced or slightly increased, respectively, in KO. The atomic force microscopy-based nanoindentation modulus were significantly lower in KO skin than WT. These data demonstrate that CypB deficiency profoundly affects Lys post-translational modifications of collagen likely by modulating LH chaperone complexes. Together, our study underscores the critical role of CypB in Lys modifications of collagen, cross-linking and mechanical properties of skin.